Concept of Europe in Consciousness of the Lithuanians (Parliamentary Studies, 2016)
Specific studies on the concept of Europe in Lithuanian are largely absent. The few studies that can be found in relation to the subject are a linguistic article by V. Rudaitienė and a book by N. Putinaitė “Trys lietuviškos Europos. Tauta, Europa, ES dabartinėje tapatybėje” (Three Lithuanian Europes: the Nation, Europe, the EU in Modern Identity) in which the author addresses the development of Lithuanians’ European identity from the perspectives of culture, philosophy and political science. It is therefore impossible to formulate what Europe is to each Lithuanian and thus a separate study needs to be conducted to address this question.Based on the data obtained from surveys and texts, a conclusion can be drawn that contemporary Lithuanians mostly associate Europe with the field of politics, with a geographical phenomenon, culture, household welfare, social sphere, and history. Respondents also emphasise the aspects of ideology and the nation, whereas the military or religion are virtually never referred to. Apart from similarities in survey and textual data, there are differences when it comes to the assessment of the above-mentioned unanimities.Lithuanians’ perceptions of Europe are shaped by historical memory, literature, and schools, however, the greatest role in the contemporary conception of Europe is played by mass media. The acquired data and its analysis leads to the conclusion that for Lithuanians Europe is a cradle of civilisation that geographically stretches from the Iberian Peninsula to the Ural Mountains and that is defined by a rich history, a simbiosos of a different cultures, nations, languages and customs, rich heritage, diverse architecture, a united community based on tolerance and equality, cooperation, democracy, and humanistic ideas. Europe can even be perceived as one large state where peace, security and justice prevail, a state that unites various independent countries and people, shares common currency and economy, and provides great oppoetunities.
Keywords: cognitive definition; discourse; concept; Europe; survey; culture